Pengujian Anomali Pasar Size Effect dan The Day of Week di Bursa Efek Indonesia - Hartoyo, Oki Tjandra Suryo; Purbawangsa, IB Anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.09.TAHUN 2018, 2018)
Capital market as a place to invest investors need to have some accurate information to consider returns and risks obtained, the existence of capital market anomaly symptoms due to the many parties and various factors involved causing the emergence of irregularities such as Size Effect and The Day of Week effect. The purpose of this study to determine the existence of irregularities of both anomalies in the Indonesia Stock Exchange.    Data sourced from sectoral shares listed on the Indonesia Stock Exchange period January 2017 - July 2017 as many as 21 companies with sampling techniques using purposive sampling method and obtained two types of groups of large capitalized stock and small capitalized stock. The analysis tools used include One Way ANOVA Test and Two Sample Tests Free Test (Independent Sample T test).    The results of the company size study there is no size effect. On the day of trading there was no anomaly symptoms of The Day of Week effect where the smallest return occurred on Tuesday (Tuesday effect) and the highest return occurred on Wednesday. The result of firm size measurement on trading day explains that there is significant difference of result due to weakness of public purchasing power of that period. Advice can be given to investors not always relying on anomalies when making investment decisions.